Madison Metro Rapid Transit Park & Ride Study: Exercising the potential of GIS to explore potential solutions to a temporal socio-environmental issue - Schoenmann, Casey; Lyons, Adam; Gillman, Wes; Kruckenberg, Sam (My University, 2011)
Identify and map suitable locations for Park & Ride lots along the periphery of the city of Madison to serve as starting points for optimal express bus routes to-and-from event locations in downtown district. The conclusions can be used to help alleviate city traffic congestion and determine future public transportation.
Includes Appendix, Figures, Maps and Bibliography.
Keywords: Park and Ride; Rapid Transit; Madison Metro; Madison, WI